Hydrolysis of oligoribonucleotides: influence of sequence and length. - Kierzek, R (1992)
The chemical stability of phosphodiester bonds of some oligoribonucleotides in the presence of a cofactor like polyvinylpyrolidine (PVP) is sequence dependent. It was found that pyrimidine-A (YA) and pyrimidine-C (YC) are especially susceptible to hydrolysis. The hydrolyzability of this same phosphodiester bond is dependent on its position in the oligomer. The presence of 3' and 5'-adjacent nucleotides enhances hydrolysis of the UA phosphodiester bond. The acceleration of the hydrolysis of UA by a 5'-adjacent nucleotide is not base dependent. However, a 3'-adjacent purine increases hydrolysis of a UA phosphodiester bond more than a 3'-pyrimidine. The presence of the exoamino group on the 3'-side base (on 6 and 4 position for adenosine and cytidine, respectively) of YA or YZ phosphodiester bond is required for hydrolysis.